The level of FoxO1 and IL-15 in skeletal muscle, serum and synovial fluid in people with knee osteoarthritis: a case control study. Issue 6 (June 2016) - Levinger, P.; Caldow, M.; Bartlett, J.; Peake, J.; Smith, C.; Cameron-Smith, D.; Levinger, I.
Abstract Summary The molecular regulation of muscle function in knee osteoarthritis is unclear. Elevated muscle atrophy regulation marker expression was associated with reduced muscle strength in knee osteoarthritis. The level of protein expression appears to be different between muscle, knee joint and serum, suggesting that inflammation is regulated differently within these tissues. Introduction Impaired muscle function is common in knee osteoarthritis (OA). Numerous biochemical molecules have been implicated in the development of OA; however, these have only been identified in the joint and serum. We compared the expression of interleukin-15 (IL-15) and Forkhead box protein-O1 (FoxO1) in muscle of patients with knee OA and asymptomatic individuals and examined whether IL-15 was also present in the joint and serum. Methods Muscle and blood samples were collected from 19 patients with knee OA and 10 age-matched asymptomatic individuals. Synovial fluid and muscle biopsies were collected from the OA group during knee replacement surgery. IL-15 and FoxO1 were measured in the skeletal muscle. IL-15 abundance was also analysed in the serum of both groups and synovial fluid from the OA group. Knee extensor strength was measured and correlated with IL-15 and FoxO1 in the muscle. Results FoxO1 protein expression was higher (p  = 0.04), whereas IL-15 expression was lower (p  = 0.02) in the muscle of the OA group. Strength was also lower in the OA group and was inversely correlated with FoxO1 expression. No correlation was found between IL-15 in the joint, muscle or serum. Conclusion Skeletal muscle, particularly the quadriceps, is affected in people with knee OA where elevated FoxO1 protein expression was associated with reduced muscle strength. While IL-15 protein expression in the muscle was lower in the knee OA group, no correlation was found between the expression of IL-15 protein in the muscle, joint and serum, which suggests that inflammation is regulated differently within these tissues. Australian Clinical Trials Registry (ACTR) number: ACTRN12613000467730 (http://www.anzctr.org.au/TrialSearch.aspx?searchTxt=ACTRN12613000467730&isBasic=True )